Bioprospecção de proteínas da esponja marinha Aaptos sp. por análise proteômica - Martins, Maria Gleiciane De Queiroz (2015)
Marine sponges are a rich reserve of natural substances, many of them of immense biotechnological interest. They comprise a promising group in providing bioactive compounds for humanity. Thus, research on new drugs from natural sources suggest that marine sponges have important bioactive compounds ponteciais: pharmacological, antimicrobial; antitumor; antiviral; anti-inflammatory; immunosuppressive; cardiovascular; neurosupressor; muscle relaxant and pollution biomarker. Analysis of expressed proteins is an important approach to determine the function of these molecules in a given organism. This study aimed to bioprospect proteins expressed by the marine sponge Aaptos sp. collected in Icarai de Amontada, Ceará, who may have biotechnological potential. For the realization of this approach were used as strategies the two-dimensional electrophoresis (2-DE) and bioinformatics. The 2-DE is a tool used to separate proteins from different organisms. Knowing the proteins expressed in the study sponge can be established Protein patterns characteristic of the species under study. Based on the above, this study used 2DE to investigate the expressed protein Aaptos sp. In order to make the extraction of total proteins was performed using 400 mg of the marine sponge Aaptos sp. For qualitative and quantitative analysis of proteins was used the method of Bradford and SDS-PAGE, respectively. From the total protein extract was determined the two-dimensional reference map for marine sponge in the study. The adjustment of images of two-dimensional gels, the protein spot detection and evaluation of data to determine apparent molecular weight (MW) and isoelectric point (pI) of the spots was made by the ImageMaster software 7. Expressed proteins were identified using the values of pI and MM spot against a UniProt protein database available on the ExPASy server. The average number of protein spots of replicas of the gels 2DE was 124. The highest abundance proteins was observed in 2DE gels in the pH range of 4 to 6.7 and with MM between 13 to 119.67 kilodalton (kDa). From the 2DE reference gel was identified 122 proteins of which 61, 46 and 15 belong to the Cnidaria taxon deuterostomia and Porifera, respectively. The proteins identified Porifera belong to functional category: ATP binding, structural component of the ribosome, catalytic activity, GTP binding, calcium ion binding and disulfide oxidoreductase activity. The functional category binding of ATP and GTP with more spots. Adicionadamente, was expressed proteins with important molecular functions already hued in the literature but not in Aaptos sp., thus indicating the importance of these marine sponges as a source of protein information that may be studied in the future for their potential use as biotechnological tools in several areas and can be used in studies to elucidate the metabolic pathways and the development of drugs against possible pathologies.